2018
DOI: 10.3390/metabo8040072
|View full text |Cite
|
Sign up to set email alerts
|

Quenching for Microalgal Metabolomics: A Case Study on the Unicellular Eukaryotic Green Alga Chlamydomonas reinhardtii

Abstract: Capturing a valid snapshot of the metabolome requires rapid quenching of enzyme activities. This is a crucial step in order to halt the constant flux of metabolism and high turnover rate of metabolites. Quenching with cold aqueous methanol is treated as a gold standard so far, however, reliability of metabolomics data obtained is in question due to potential problems connected to leakage of intracellular metabolites. Therefore, we investigated the influence of various parameters such as quenching solvents, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Alternatively, the spent medium can be initially removed by centrifugation or rapid filtration prior to freezing or quenching in cold methanol, hot methanol or ethanol, or perchloric acid. 6,9,10 Prior studies have compared an array of quenching methods for metabolomics analysis of bacteria, 8,11,12 yeast, 12,13 algae, 14 and mammalian cells, 6 but the optimal method was often found to be metabolite-and organism-specific. Therefore, refining and expanding upon current methods to assess metabolic quenching efficiency is expected to facilitate the application of metabolomics to new organisms and experimental systems.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the spent medium can be initially removed by centrifugation or rapid filtration prior to freezing or quenching in cold methanol, hot methanol or ethanol, or perchloric acid. 6,9,10 Prior studies have compared an array of quenching methods for metabolomics analysis of bacteria, 8,11,12 yeast, 12,13 algae, 14 and mammalian cells, 6 but the optimal method was often found to be metabolite-and organism-specific. Therefore, refining and expanding upon current methods to assess metabolic quenching efficiency is expected to facilitate the application of metabolomics to new organisms and experimental systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Commonly used metabolic quenching methods include directly mixing cell culture samples with a quenching solution selected from a variety of possible options, such as cold methanol solutions, , cold media, or cold saline ice slurries. Once quenched, the cell biomass can be physically separated from the spent medium and quenching solution prior to freezing or immediate metabolite extraction. Alternatively, the spent medium can be initially removed by centrifugation or rapid filtration prior to freezing or quenching in cold methanol, hot methanol or ethanol, or perchloric acid. ,, Prior studies have compared an array of quenching methods for metabolomics analysis of bacteria, ,, yeast, , algae, and mammalian cells, but the optimal method was often found to be metabolite- and organism-specific. Therefore, refining and expanding upon current methods to assess metabolic quenching efficiency is expected to facilitate the application of metabolomics to new organisms and experimental systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample collection for metabolomics strive to capture the metabolic state of the sample at the time of sampling and therefore the it should alter the metabolome as little as possible as well as quench the metabolism as quickly as possible to avoid metabolite degradation post-sampling. Furthermore, factors such as sampling, quenching the metabolism, storage conditions as well as sample extraction parameters have great effects on the final metabolome as well as data quality Engskog et al (2016) , Vuckovic (2018) , and have been investigated and reviewed for plasma, serum and urine Bi et al (2020) , González-Domínguez et al (2020) , Smith et al (2020) , mammalian cells Dettmer et al (2011) , Bi et al (2013) , Engskog et al (2015) , bacteria and microbes Mashego et al (2007) , Rabinowitz (2007) , Kapoore and Vaidyanathan (2018) , as well as for plants ( Kim and Verpoorte, 2010 ; Rodrigues et al, 2019 ; Salem et al, 2020 ). For the collection of sponges for metabolomics, no guidelines or practical consensus exist and the procedures for sampling varies, in some cases the sponges are frozen directly upon collection, in some cases the time between collection and freezing is not stated in the publications and in some cases the sponges are immediately stored in ethanol where after the ethanol is often discarded prior to extraction of the sponge ( Olsen et al, 2016b ; Einarsdottir et al, 2017 ; Bayona et al, 2018 ; Bayona et al, 2020 ; Reverter et al, 2018 ; Mohanty et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Bolten et al (2007) reported potential problems connected to the leakage of intracellular metabolites with cold methanol quenching. Kapoore and Vaidyanathan (2018) investigated the influence of various parameters such as quenching solvents, methanol concentrations and inclusion of buffer additives on intracellular metabolite leakage from Chlamydomonas reinhardtii. They reported a significant loss of intracellular metabolites with the use of the conventional 60 % (v/v) methanol, and they recommended the supplementation of 70 mM HEPES to reduce the leakage of metabolites.…”
Section: Bioreactor Effluentmentioning
confidence: 99%